Academic Literacy through Online Academic Writing Classes for University Students - Wahyu Febri Ramadhan Sudirman; Paisal Paisal; Ramadhaniati Fitri (Global Sustainability Research Institute, 2026)
Academic literacy has become one of the essential competencies that higher education students must possess to support research activities and scientific publication. However, many students continue to encounter challenges in identifying research ideas, formulating research gaps, conducting literature reviews, organizing scientific manuscripts, and utilizing reference management applications. This community service program aimed to strengthen students' academic literacy and academic writing competencies through an online literacy class. The activity was conducted using a training and mentoring approach through Zoom Meeting, involving students from Universitas Patompo as participants. The program consisted of interactive lectures, demonstrations, discussions, question-and-answer sessions, and practical exercises covering research idea exploration, research gap identification, literature searching, IMRAD-based article writing, reference management using Mendeley, and publication strategies. The implementation demonstrated high participant engagement, as reflected by active discussions and questions throughout the webinar. Participants showed improved understanding of scientific writing principles, research planning, literature synthesis, and reference management. The online learning approach also facilitated flexible interaction between presenters and participants while promoting collaborative learning. Overall, the program successfully enhanced participants' academic literacy, academic writing skills, and confidence in preparing scientific manuscripts. This activity indicates that online literacy training can serve as an effective strategy for strengthening students' research capacity and fostering a sustainable culture of scientific writing in higher education.